1996
DOI: 10.1002/ctpp.2150360405
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics and Chemical Quasi‐Equilibria of the Ozone Synthesis in Oxygen DC Discharges

Abstract: The spatial distribution of ozone and of oxygen atoms was studied along the active and the passive zone of a dc discharge (positive column, pressure: p = ( 4 . . .lo) . 10' Pa, current: I = 2 . . .50 mA, flow rate: F = 5 . . .lo0 sccm) in flowing oxygen. The composition of the final output 02/03-mixture is controlled by relaxation processes in the passive reactor zone. It is affected sensitively by the total number density and the gas temperature in the afterglow. Steady states meaning reversible chemical qua+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…This is due to the fact that ozone is formed and destroyed effectively by species, such as O and O 2 (a 1 Δ g ), that survive the chemical climate of a discharge on the time scale of milliseconds, unlike ionic and highly excited species that exist on the microsecond time scale only. Quasi equilibrium concentrations of O 3 are thus almost independent of the discharge conditions, which may vary from a very low degree to complete oxygen dissociation . In agreement with these findings of Jacobs et al, we will thus adopt the picture according to which the gas is first excited in the active zone of the discharge reactor and ozone and then finally forms in the afterglow region, when O atoms and O 2 (a 1 Δ g ) fade away (see Figure 12 of ref ).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…This is due to the fact that ozone is formed and destroyed effectively by species, such as O and O 2 (a 1 Δ g ), that survive the chemical climate of a discharge on the time scale of milliseconds, unlike ionic and highly excited species that exist on the microsecond time scale only. Quasi equilibrium concentrations of O 3 are thus almost independent of the discharge conditions, which may vary from a very low degree to complete oxygen dissociation . In agreement with these findings of Jacobs et al, we will thus adopt the picture according to which the gas is first excited in the active zone of the discharge reactor and ozone and then finally forms in the afterglow region, when O atoms and O 2 (a 1 Δ g ) fade away (see Figure 12 of ref ).…”
Section: Resultssupporting
confidence: 76%
“…Quasi equilibrium concentrations of O 3 are thus almost independent of the discharge conditions, which may vary from a very low degree to complete oxygen dissociation . In agreement with these findings of Jacobs et al, we will thus adopt the picture according to which the gas is first excited in the active zone of the discharge reactor and ozone and then finally forms in the afterglow region, when O atoms and O 2 (a 1 Δ g ) fade away (see Figure 12 of ref ). Ozone produced in an electric discharge can thus be expected to acquire, at least to a large extent, its isotopic composition from the formation processes according to eq or eq , which has led us to adopt the isotope approach depicted in eq .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This is due to two reasons. First, for a wide range of ionization and dissociation conditions ozone gross production in plasma reactors is dominated by reactions of the neutral ground state constituents [ Jacobs et al , 1996]. Second, the similar isotopic composition of ozone [ Morton et al , 1990] from electric discharge experiments and from photolysis recycling studies, the latter ensuring reactants to be in their electronic ground state, indicates that ground state kinetics if not completely, at least largely, determines the isotopic composition of ozone, even under discharge conditions.…”
Section: Isotopologue Enrichments In a Closed Systemmentioning
confidence: 99%
“…This is because the ozone formation in a Tesla discharge has been shown to be dominated by neutral O-atoms and O 2 molecules in their ground state. 19 In addition, the ozone experiments by Bhattacharya et al 7 demonstrated that photolysis and discharge experiments lead to similar internal isotopic distribution. In their study, the UV photolysis of oxygen was done by varying pressure whereas the Tesla discharge was done by varying both pressure (P) and temperature (T).…”
Section: Chemical Kinetics Simulation and Changes In Rate Constamentioning
confidence: 98%